2018
DOI: 10.1159/000489091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Phonological Reading and Writing Remediation Program in Students with Dyslexia: Intervention for Specific Learning Disabilities

Abstract: Objective: To determine the effects of a phonological remediation reading and writing program in individuals with dyslexia, through behavioral and objective evaluations. Patients and Methods: Twenty children diagnosed with dyslexia, aged 8–14 years, were included in this study. Group I (GI) was composed of 10 children who took part in the program, and group II (GII) consisted of 10 subjects who did not take the remediation. The pre-testing evaluated phonological awareness, rapid naming, working memory, reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…Therefore, it is speculated that due to the common phonologal base de cit between these abilities (PA, VSTM and RAN), intervention of one of them will transfer improvement to the others. The results of our trial are in line with other studies that have shown that with the PA intervention, improved RAN and VSTM (10,17,19,20). The rst study on the in uence of PA training on improving verbal WM was conducted by Gillam and van Kleeck (9).…”
Section: Discussonsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, it is speculated that due to the common phonologal base de cit between these abilities (PA, VSTM and RAN), intervention of one of them will transfer improvement to the others. The results of our trial are in line with other studies that have shown that with the PA intervention, improved RAN and VSTM (10,17,19,20). The rst study on the in uence of PA training on improving verbal WM was conducted by Gillam and van Kleeck (9).…”
Section: Discussonsupporting
confidence: 91%
“…They concluded that PA and RAN training affect sub-lexical spelling (decoding) and reading speed, respectively and are independent abilities (12). Evidence shows that although RAN, VSTM and PA are independent, phonological training enhances RAN (10,(16)(17)(18) and VSTM (19)(20)(21). In one study, children who received RAN intervention did not show improvement in RAN (22) and since PA tasks also involve VSTM, PA intervention results in VSTM enhancement (21).…”
Section: Introductionmentioning
confidence: 99%
“…https://osf.io/8r6zf/ (Schmalz, 2018). Unfortunately, we could not find an appropriate database for Brazilian Portuguese, therefore we could not calculate onset entropy for Ferraz et al (2018).…”
Section: Quantifying Orthographic Depthmentioning
confidence: 99%
“…The moderator analysis showed that NRCTs or cRCTS found a higher mean effect size (g' = 0.70, 95% CI [0.26 -1.14]) than RCTs (g' = 0.53, 95% CI [0.36 -0.70]), but this difference did not reach statistical significance (p = 0.510). Five studies used non-standardized tests to evaluate at least one of the outcome measures (Arnbak & Elbro, 2000;Ferraz et al, 2018;Gustafson et al, 2007;Kast et al, 2007;Oakland et al, 1998). Analyses showed a higher mean effect size for standardized tests (g' = 0.62, 95% CI [0.42 -0.82]) than for nonstandardized measures (g' =0.29, 95% CI [-0.00 -0.58]), but again no significant difference (p = .072).…”
Section: Study Qualitymentioning
confidence: 99%
“…Literature points out different ways to work with children with reading and writing difficulties, among which these can be mentioned: training phonological awareness ability [10][11][12] , used especially in children with reading difficulty by phonological route (literacy process); working with various linguistic aspects, such as vocabulary and/or listening comprehension 12,13 ; training based on producing narratives/sharing story reading 1,13,14 ; and, training working memory (WM) ability [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%